Longer—but Harder—Lives?: The Hispanic Health Paradox and the Social Determinants of Racial, Ethnic, and Immigrant–Native Health Disparities from Midlife through Late Life - Boen, Courtney E.; Hummer, Robert A. (Journal of health and social behavior, 2019)
Though Hispanics live long lives, whether a “Hispanic paradox “extends to older-age health remains unclear, as do the social processes underlying racial-ethnic and immigrant-native health disparities. Using data from the Health and Retirement Study (2004–2012; N = 6,581), we assess the health of U.S.- and foreign-born Hispanics relative to U.S.-born whites and blacks and examine the socioeconomic, stress, and behavioral pathways contributing to health disparities. Findings indicate higher disability, depressive, metabolic, and inflammatory risk for Hispanics relative to whites and similar health profiles among Hispanics and blacks. We find limited evidence of a healthy immigrant pattern among foreign-born Hispanics. While socioeconomic factors account for Hispanic-white gaps in inflammation, disparities in other outcomes persist after adjustment for socioeconomic status, due in part to group differences in stress exposure. Hispanics may live long lives, but their lives are characterized by more socioeconomic hardship, stress, and health risk than whites and similar health risks as blacks.